Enthalpy of solvation of butanediols in different solvents - Jesus, A. J. Lopes (2000)
The enthalpies of solution for 1,2-, 1,3-, 1,4- and 2,3-butanediol in water, formamide and dimethylsulphoxide were determined by calorimetry. From the results and data available in the literature for the enthalpy of vaporisation, the enthalpy of solvation was determined. The enthalpy of solvation was decomposed into two terms, cavity formation in the solvent to hold the solute and solute-solvent interaction.